2019
DOI: 10.3390/ma12182923
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Alginate-Based Green Packaging Films Functionalized by Guava Leaf Extracts and Their Bioactivities

Abstract: The aim of this work was to develop green and bioactive films with sodium alginate incorporating guava leaf extracts. Seven formulations were performed with a different sodium alginate: Guava leaf water extract (WE)/ethanolic extract (EE) proportions (100:0, 90:10, 85:15, 80:20), and glycerol were used as a plasticizer. The HPLC-PDA analysis showed the main phenolic compounds in WE were gallic acid, ellagic acid, quercetin-3-O-β-D-xylopyranoside, avicularin and quercetin. The main polyphenols in EE were rutin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 38 publications
9
42
0
Order By: Relevance
“…SA/guava leaf extract composite film was prepared by Luo et al Due to the hydrogen interaction between SA and guava leaf extract, the structure of the composite film was more compact, which improved the TS of the composite film. However, the excessive ratio of extract may lead to uneven dispersion in the mixture, resulting in the decrease in TS [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…SA/guava leaf extract composite film was prepared by Luo et al Due to the hydrogen interaction between SA and guava leaf extract, the structure of the composite film was more compact, which improved the TS of the composite film. However, the excessive ratio of extract may lead to uneven dispersion in the mixture, resulting in the decrease in TS [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al also suggested that the strong interfacial interaction between phenolic compounds and sodium alginate may improve the moisture resistance. However, the high content of phenolic compounds may accumulate in the polymer matrix to produce voids, resulting in a higher WVP value [ 37 ]. Compared with the SA/guava leaf extract composite film (0.55–0.75 × 10 −11 g/m·s·Pa), the WVP value of the film had no significant difference, and the water vapor barrier of the two films was better [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations